DABCO‐Catalysed One‐Pot Eco‐Friendly Synthetic Strategies for Accessing Pyranochromenone and Bis(benzochromenone) Compounds. Issue 45 (4th December 2018) - Bagchi, Sourav; Monga, Aparna; Kumar, Sagar; Deeksha,; Sharma, Anuj
Abstract: An easy, facile and mild approach of liquid assisted grinding for the synthesis of novel dihydrobenzo[f]pyrano[3, 2‐c]chromenone derivatives using multicomponent cascade is herein described. The advantages of this protocol is one pot strategy, high reaction throughput, excellent yields, diversified scope, excellent score of green matrices. In addition, synthesis of bis(benzo[f]chromen‐3‐one) derivatives under microwave irradiation have also been established. The current methods utilize DABCO as a catalyst in forging these bioactive molecules. Also, all the final products are obtained by mere filtration, and the reaction conditions do not require any harsh reagents or typical work up. Abstract : DABCO‐catalysed liquid assisted hand grinding (LAG) synthesis of novel dihydrobenzo[ f ]pyrano[3, 2‐ c ]chromenone derivatives have been established. The method score well in green matrices calculation. In addition to it, the synthesis of bis(benzo[ f ]chromen‐3‐one) derivatives under microwave irradiation have also been proposed. Moreover, this method is completely column‐free.